Preto e branco, azul e vermelho: cultura popular, tempo e literatura no Jornal Nação Cariri (1980-1987) - Fonteles, Kalil Tavares (2021)
This study aims to read and understand a historical conflict. The 1980s in Brazil takes as one of its endless questions the theme of Popular Culture, but more specifically the “Brazilian people” considered as an intellectual and cultural object. Based on the most identified debate in many groups of intellectuals in the 1960s, such as the Popular Culture Centers (CPC's), the main consequence of this conflict is the possibility (or not) of pursuing a problem of culture, and more specifically of written culture: Where to find the popular? Is it possible to locate in a place beyond writing what has always retained it in a permanent intellectual project? Based on the textual corpus of that period, it is possible to locate in the Nação Cariri’s archives, a culture newspaper published between 1980 and 1987, another path within the critical resumption from the poetic writing of the object, of the absent, of the people. Other forms of narrating the popular are based there, either through articles, reports, and “committed” studies or through poems, since Nação Cariri's efforts to establish itself as a publication of artists and poets is poignant.